2016
DOI: 10.20533/iji.1742.4712.2016.0145
|View full text |Cite
|
Sign up to set email alerts
|

Alternative E-learning Assessment by Mutual Constrain of Responsive and Constructive Techniques of Knowledge Acquisition Evaluation

Abstract: Innovation on e-assessment is presented. Here, 43 bachelor students´ conceptual definitions to a course schema related concepts are obtained by using a natural semantic network technique. This allowed implementing a constructive assessment technique of students´ that is complemented by a responsive assessment of student´s learning based on semantic priming studies. It is argued that by using both assessment approaches in a dynamic mutually constrained way a new alternative approach to eassessment can be implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In this proposal, assessment is assumed to exert effects at various levels, and it constitutes by itself a domain and a goal. An e-assessment system that complies with these evaluation requirements, implementation viability, and cognitive science principles was first presented by Morales and colleagues [33][34][35].…”
Section: Adaptive Instruction and The Constructive/chronometric E-assmentioning
confidence: 99%
See 1 more Smart Citation
“…In this proposal, assessment is assumed to exert effects at various levels, and it constitutes by itself a domain and a goal. An e-assessment system that complies with these evaluation requirements, implementation viability, and cognitive science principles was first presented by Morales and colleagues [33][34][35].…”
Section: Adaptive Instruction and The Constructive/chronometric E-assmentioning
confidence: 99%
“…On the other hand, it is not necessary to specify a lexicon; it is enough to say that lexical information is obtained and organized as proposed by a no-lexicon view. Figure 7B shows that this effect might vary depending on the knowledge domain and the effect of instruction [34,37,39].…”
Section: Empirical Support For E-assessment Based On the Human Lexiconmentioning
confidence: 99%
“…Semantic priming techniques are well-suited to study knowledge organization in the human lexicon (Mcnamara, 2005). As will be described later, Morales and colleagues (Gonzales, et al, 2013;Morales, Lopez & Velasco, 2016) have shown that by considering the schemata priming effect (Lopez, & Theios, 1996), it is possible to differentiate from students who have assimilated long-term knowledge (e.g., Becker, Moscovitch, Behrman & Joordens, 1997) from the students who have not assimilated long-term knowledge.…”
Section: Figure 2 Concepts Related By Schemata Course Content Are Sementioning
confidence: 99%
“…Moreover, computer cognitive reports (Figure 2-E) provide users with a comparative concept organization between a teacher and a student's mental representation (D). Morales, Lopez & Velasco, 2016;Lopez, Morales, Hedlefs, Gonzalez, 2014).…”
Section: Cr E-assessment As a Framework For E-learning Research And Dmentioning
confidence: 99%
See 1 more Smart Citation